Clean energies in Mexico: projections for solar energy - Petrarca, Rocco (Revista Internacional de Salarios Dignos, 2021)
In this research we analyze the current situation and prospects for solar energy generation in Mexico in order to identify areas of opportunity for both investment for private initiative and intervention for public policies. Methodology. Based on the official data provided by the Ministry of Energy, a forecasting model is built from an autoregressive time series model (AR1). The main results indicate that the generation of energy from clean sources such as solar has a negative trend in Mexico, so it is urgent that the government incentivize the sector so that it is attractive to investors and the country can eventually transition from a model from combustion energy to green energy. One of the main limitations was access to updated data, so information was only available until December 2017. However, the resulting model fit is quite reliable to forecast the behavior of the following years. The results give sufficient evidence of the urgency of intervention in the renewable energy sector in Mexico, abandoned in the most recent energy reform. Originality / value of the paper. The paper places the accent on the green energy sector in the midst of a great global economic crisis that collapsed oil prices to negative values and called into question the continuity of the rentier model for producing countries. It is an alert to initiate the transition of the energy paradigm.